Heat tolerance in Â½ senepol- and â… holstein - â…œ brahman crossbred calves - Quintero Moreno, Armando; Calatayud, Derwin; Boscán, Julio; Rojas, Nidia; Arrieta, Darwuin (Revista Científica de la Facultad de Ciencias Veterinarias)
Two trials were conducted to determine heat tolerance between crossbred ½ Senepol- (S-) and â… Holstein-â…œ Brahman (HB). Differences between crossbred in trial 1, and crossbred and ambient temperature (Ta: 25 and 34°C) in trial 2 were evaluated through rectal temperature (Tre), respiration rate (RR), heat tolerance index (HTC), coefficient of adaptability (CA), average daily gain (ADG), and plasma cortisol. Trial 1 used 324 observations in 18 S- calves and 12 HB calves, while trial 2 used 90 observations in 8 S- calves and 7 HB calves. The statistical analysis of the parameters evaluated was carried out by mixed model with repeated measurements, whilemeans the ADG was perform by T-test. In trial 1, S- and HB calves had similar heat tolerance (P>0.05). In trial 2, Tre and RR in HB were greater (P menor 0.05) than S- calves, and also HTC, CA and ADG were the best in S-. At 34°C of Ta, the HB calves had significantly (P menor 0.05) greater Tre, and lower HTC than Scalves (P menor 0.01). The results demonstrate the great heat tolerance of the crossbred Senepol.